A medical audit of the management of Cryptococcal Meningitis in HIV patients in the Cape Winelands (East) District, Western Cape, South Africa - Von Pressentin, Klaus Botho (Stellenbosch : Stellenbosch University, 2017)
ENGLISH SUMMARY : Introduction: This thesis summarises the findings of a medical audit on the management of Cryptococcal Meningitis (CM). The study population of HIV positive adults (N = twenty five) were admitted during November 2009 – June 2010 to five hospitals of the Cape Winelands (East) District, Western Cape, South Africa. In the context of the HIV pandemic, CM has become the most common cause of community-acquired meningitis, and has poor outcomes if left untreated. The South African HIV Clinician Society has published treatment guidelines in 2007. These guidelines have been used by the audit team to compile a list of measurable criteria (with set targets) to evaluate the structure, process and outcome of CM management. A pilot audit (2008) at the regional hospital has demonstrated that certain target standards were not met. Aims and Objectives: The aim was to improve the quality of the clinical care of HIV-patients diagnosed with CM in the Cape Winelands (East) district. The objectives included the review of the audit criteria and target standards, demonstrating improvement in quality of CM care at the Level 1 and 2 hospitals, identifying new interventions based on the findings and providing recommendations to the health facilities. Methods: In 2009, the researcher formed a new audit team, reviewed the audit criteria and held teaching interventions based on the national treatment guidelines. An intervention, based on the findings of the pilot audit, aimed at improving the clinical team’s adherence to the treatment guidelines. Results: The audit identified the following areas that did not meet the target standards: the availability of Amphotericin B (Ampho B) and spinal manometers; the use of manometry in all initial lumbar punctures (LPs); completing fourteen days of the required Ampho B treatment; renal monitoring in patients on Ampho B; commencement of antiretroviral treatment (ART) by week four; and, the two-month survival figures post-diagnosis. The re-audit at the Level 2 hospital highlighted the need for improved medical record keeping to aid the audit process. Arrangement of inpatient ART counselling happened more consistently at the Level 1 hospitals. Adherence to the ART target and measures to prevent Ampho B related morbidity is comparable to that of the Level 2 hospital. The audit has also provided insight to the researcher and audit team on the practical challenges of conducting a prospective data collection technique across different care settings. Recommendations Level 1 hospitals should continue to manage CM patients. The availability of spinal manometers and closer adherence to renal monitoring require attention. Formal feedback to the audit team and clinical teams is planned. A multimodal interdisciplinary Quality Improvement approach (such as an integrated care pathway) is recommended and a future re-audit is encouraged to assess improved adherence to the CM management guidelines. The buy-in of stakeholders (management, health care workers and patients), the ongoing support of an audit team and a committed Quality Improvement environment will allow the medical audit process to become ingrained in the South African public healthcare setting.